The Shelf Life of Incumbent Workers during Accelerating Technological Change: Evidence from a Training Regulation Reform - Simon Janssen; Jens Mohrenweiser (Institute of Labor Economics (IZA), 2018)
In periods of accelerating technological change, incumbent workers must continuously update their skills to remain productive. In contrast, high school or college graduates recently entering the labor market often have the most up-to-date skills. We investigate how incumbent workers' careers respond to the increasing labor supply of graduates with more technologically advanced IT skills during a period of accelerating technological change. We identify a supply shock of more technologically advanced IT-skilled graduates by exploiting a reform of a German training regulation, a reform mandating all new apprentices in a large manufacturing occupation to acquire in-depth IT skills. We use a difference-in-differences approach to analyze how this supply shock of IT-skilled workers affected the careers of incumbent workers. The results show that even young incumbents experienced long-lasting earnings losses in the form of lower wage growth after the IT-skilled graduates entered the labor market. A detailed analysis of the mechanisms suggests that incumbents on average forwent promotions and technologically advanced IT-skilled graduates crowded incumbents out of their occupation. However, despite losing their occupation, incumbents experienced relatively little unemployment during the transition period following the supply shock and on average resumed stable careers in other occupations and sectors.
Keywords: J24; J64; O30; 330; skill-biased technological change; wage adjustments; supply shock; apprenticeship